Tata Laksana Perioperatif Pada Single Ventricle - Riza Cintyandy; Cindy E Boom (Jurnal Kardiologi Indonesia, 2012)
Single Ventricle (SV) was a terminology for a condition when one of theventricles is hypoplastic or absent. These patients often require a seriesof procedures to provide effective palliation. Surgical therapy commitsthe single ventricle to the delivery of oxygenated blood to the systemiccirculation and deoxygenated blood is directed to the pulmonary circulationbypassing the ventricle. There are three phases of palliation procedures: (1)placement of shunt, (2) Bidirectional Glenn Shunt and (3) Fontan procedure.There are different physiologies in each phase. With improved surgicaltechniques and medical care, SV patients are living longer. Many SV patientsappear in need of anesthesia for routine general and obstetric procedures.Anesthesiologists, general practitioners, and subspecialists alike increasinglymay encounter the patient with SV physiology.